The Relationship Between Depression Levels and Antisocial Behavior Among Students in the Faculty of Medicine at Nusa Cendana University - Saka Pamukti Supriyadi; Conrad Liab H. Folamauk; Rr. Listyawati Nurina (CV. Publikasi Indonesia, 2026)
The prevalence of psychological distress among medical students is higher than that of the general population, with depression being one of the most commonly reported conditions. Psychosocial disorders, such as stress and depression, may develop into more severe depressive disorders and antisocial behavior if left untreated. This study aimed to identify the relationship between depression levels and antisocial behavior among students at the Faculty of Medicine, Nusa Cendana University. A cross-sectional design was employed in this study. The sample consisted of 122 students from the Faculty of Medicine, Nusa Cendana University, from the 2017, 2018, and 2019 cohorts. Depression levels were measured using the validated Beck Depression Inventory-II (BDI-II) questionnaire, while antisocial behavior was assessed using the Subtypes of Antisocial Behavior (STAB) questionnaire. Data were analyzed using Somers’ d correlation test. The results showed that 86 respondents (70.49%) had minimal or no depression, 19 respondents (15.57%) had mild depression, 11 respondents (9.02%) had moderate depression, and 6 respondents (4.92%) had severe depression. Regarding antisocial behavior, 109 respondents (89.34%) demonstrated low levels of antisocial behavior, 13 respondents (10.66%) demonstrated moderate levels, and no respondents exhibited high levels of antisocial behavior. The analysis revealed a p-value of 0.001 (α < 0.05), indicating a statistically significant relationship between depression levels and antisocial behavior among students. Therefore, this study concluded that depression levels were significantly associated with antisocial behavior among students at the Faculty of Medicine, Nusa Cendana University (p = 0.001).